Symbiotic Organism Search Based on Sensitivity Factor for Optimal Location and Sizing of Distributed Generation - Iswan Iswan; Umar Umar; M Natsir Rahman; Suparman Suparman; Muhammad Said; Faris Syamsuddin; Dharmawan Dharmawan; Andi Syarifuddin (Universitas Khairun, 2025)
The technology of Distributed Generations (DGs) has attracted the focus of researchers and engineers over the past two decades as an effective solution to address power quality and supply issues for customers. Determining the optimal locations and sizes for DGs remains a significant challenge. This study explores the optimization of DG placement and sizing to reduce power losses in radial distribution systems. The Loss Sensitivity Factor (LSF) is used to identify suitable locations for DGs, while Symbiotic Organisms Search (SOS) is utilized to determine their capacities. Simulation results using three DGs on the IEEE 33-bus distribution system indicate that this approach can reduce active power losses by 67.66%.